Exploring workplace bullying from diverse perspectives: A Journal of Applied Communication Research forum. Issue 6 (1st November 2020) - Tye-Williams, Stacy; Carbo, Jerry; D'Cruz, Premilla; Hollis, Leah P.; Keashly, Loraleigh; Mattice, Catherine; Tracy, Sarah J.
ABSTRACT: Workplace bullying is a pernicious workplace problem that harms employees and organizations alike. Targets suffer mental and physical consequences of repeated abuse. Organizations experience consequences such as diminished worker productivity and increased turnover. In some cases, even workplace violence. While these instances are thankfully rare, it is important to understand how workplace bullying manifests in organizations and what employees, bystanders, and organizations can do about it. At the invitation of the editor to convene a diverse panel of experts on workplace bullying, seven scholars responded to questions pertaining to six workplace bullying-related issues. These are conceptual definition; bystander intervention; the relationship between race, gender, and other marginalized identities and workplace bullying; interdisciplinary opportunities and constraints; developments in United States policy; and how employees, bystanders, and organizations can and should respond to workplace bullying.